Due Process in Financial Accounting - Kasingku, Frisky Jeremy (SAFE-Network, 2023)
This study intends to descriptively elaborate on the due process of standard-setting in Financial Accounting. A literature review is conducted to explain the due process concept. This study discusses the importance of developing or creating standards in Financial Accounting, the standard-setting in various countries, and the uses of due process in developing the standards. As a result, it was found that the standard-setting process is affected heavily by political factors. Standard setters, Financial Accounting Standard Board, and International Accounting Standard Board cannot avoid political factors in developing or creating the standards. Consequently, due process is used to formulate the standards to facilitate the political factors in setting the accounting standards.